Analysis of Varved Sediment and Weather Relationships in Lake Linnè, Svalbard - Wei, Jeremy (2012)
The recent debate involving climate change has become increasingly important in the past decade. Arctic environments are important locations for study as they are particularly sensitive to climate variations. Proglacial lake sediments, particularly varves, such as those found at Lake Linnè, on the island of Spistbergen, Svalbard, demonstrate this sensitivity as they are driven by glacial ablation. The correlation of cores from different lake locations has served to identify and discard inconsistencies in the varve record. The relationship between measured varve thickness and weather parameters is based on meteorological records for the past century, and demonstrates the responsiveness of varves to changes in climate and weather as glaciers are sensitive to these changes. The measuring and counting of varves allows the construction of a chronology which can therefore serve as a climate proxy for Svalbard for the past century. The varve analysis from this study reveals the complexity of the sedimentation in Lake Linnè, and attempts to define the other likely factors which contribute to varve deposition. Overall, the assembled climate relationships reveal varves which can be linked to changes in weather and climate patterns, and the possibility of increased sensitivity of the Lake Linnè proglacial system to climate change. The National Science Foundation, The Svalbard REU